Clinical Lactation Studies of Lithium: A Systematic Review - Imaz, Maria Luisa; Torra, Mercè; Soy, Dolors; García-Esteve, Lluïsa; Martin-Santos, Rocio (Frontiers in Pharmacology, 2019)
Background: There is substantial evidence that postpartum prophylaxis with lithium lowers the rate of relapse in bipolar disorder. However, it is contraindicated during breastfeeding due to the high variability of the transfer into breast milk. Aims: We conducted a systematic review of the current evidence of studies assessing the transfer of lithium to lactating infants and short-term infant outcomes. Methods: An a priori protocol was designed based on PRISMA guidelines. Searches in Pubmed and LactMed were conducted until September 2018. Studies assessing lithium pharmacokinetic parameters and short-term infant outcomes were included. Quality was assessed using a checklist based on international guidelines (i.e FDA). Results: From 344 initial studies, 13 case reports/series with 39 mother-child dyads were included. Only 15% of studies complied with ≥50% of the items on the quality assessment checklist. Infants breastfeed a mean (SD) of 58.9 (83.3) days. Mean maternal lithium dose was 904(293) mg/day; corresponding lithium plasma/serum concentration was 0.73(0.26) mEq/L and breastmilk concentration 0.84(0.14) mEq/L. Mean infant lithium plasma/serum concentration was 0.23(0.26) mEq/L. Twenty-six (80%) infants had concentrations ≤0.30 mEq/l without adverse effects. Eight (20%) showed a transient adverse event (i.e. acute toxicity or thyroid alterations), and two (5%) congenital malformations (cardiovascular and reproductive systems). All of them were also prenatally exposed to lithium monotherapy or polytherapy. Conclusion: The current evidence comes from studies with a degree of heterogeneity and of low-moderate quality. However, it identifies areas of improvement for future clinical lactation studies of lithium and provides support for some clinical recommendations.